Pengaruh Integrated Marketing Communication terhadap Keputusan Mendaftar Siswa pada PKBM Kendedes - Michelle Janette Hosea (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Education is a planned process that supports students' potential development. PKBM Kendedes in Malang City serves as an alternative non-formal education provider offering life skills programs. This study aims to analyze the influence of Integrated Marketing Communication (IMC) on students’ enrollment decisions. A quantitative approach is used to evaluate IMC strategies such as Advertising, Sales Promotion, Public Relations, Personal Selling, WOMM, Direct Marketing, and Direct Marketing implemented by the institution. The research is expected to enrich IMC theory in the context of alternative education institutions and provide strategic guidance for PKBM Kendedes in enhancing promotional effectiveness.